2007
DOI: 10.1002/ptr.2317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous‐ethanol extract from Crocus sativus (saffron) on guinea‐pig isolated heart

Abstract: In this study, the effects of an aqueous-ethanol extract from Crocus sativus on heart rate and contractility were examined. Isolated guinea-pig hearts were perfused through the aorta in a Langendorff mode. Heart rate and contractility were determined in the presence of four concentrations of the extract (0.1, 0.5, 1.0 and 5.0 mg%) and diltiazem (0.1, 1, 10 and 100 microm) in perfused heart with: (1) ordinary Krebs solution (group 1, n = 9), (2) calcium-free Krebs solution (group 2, n = 7). In group 1, three hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 12 publications
1
48
0
Order By: Relevance
“…In agreement with previous findings, our study confirmed the depressant effect of saffron on atrio-ventricular conductivity as PR prolongation and lengthening of the refractory period as QTc prolongation in the in vivo model. On the other hand, it is documented that the extract of saffron has a potent inhibitory effect on the calcium channel of guinea-pig isolated heart (Boskabady et al, 2008). Inhibition of calcium channel can cause the reduction of the slope of pacemaker potential, and hence slowing the electrical conductivity of the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with previous findings, our study confirmed the depressant effect of saffron on atrio-ventricular conductivity as PR prolongation and lengthening of the refractory period as QTc prolongation in the in vivo model. On the other hand, it is documented that the extract of saffron has a potent inhibitory effect on the calcium channel of guinea-pig isolated heart (Boskabady et al, 2008). Inhibition of calcium channel can cause the reduction of the slope of pacemaker potential, and hence slowing the electrical conductivity of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Saffron through prolonging the action potential and effective refractory period, seen as prolonged QT interval on ECG, may prevent the occurrence of the re-entry currents and hence lethal ventricular arrhythmias. On the other hand, regarding the inhibitory effect of saffron on calcium channels (Boskabady et al, 2008), similar to anti-arrhythmic drugs of class 4, it is possible that a part of its anti-arrhythmic effect prevents calcium entry into cells during heart ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant negative correlations between concentrations of the extract and diltiazem and their effects in both groups (p<0.01 to p<0.001). The results suggested a potent inhibitory effect of aqueous-ethanol extract from Crocus sativus on the calcium channel of guinea-pig heart [113].…”
Section: Crocus Sativusmentioning
confidence: 89%
“…It has been shown that the aqueous-ethanol extract of C. sativus possesses a potent inhibitory effect on heart rate and contractility of guinea pig heart via calcium channelblocking effect (25). Furthermore, the hypotensive effect of C. sativus petals extract has been shown in rats (26).…”
Section: Introductionmentioning
confidence: 99%